Antibacterial activity of endophytic fungi isolated from the stem bark of jambu mawar (Syzygium jambos) - KURRATUL ‘AINI; ELFITA ELFITA; HARY WIDJAJANTI; ARUM SETIAWAN; ALFIA R. KURNIAWATI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. ‘Aini K, Elfita, Widyajanti H, Setiawan A, Kurniawati AR. 2021. Antibacterial activity of endophytic fungi isolated from the stem bark of jambu mawar (Syzygium jambos). Biodiversitas 23: 521-532. Syzygium jambos (jambu mawar) is widely used in South Sumatra as a traditional medicine to treat various diseases, including pathogenic bacterial infections. Literature studies report that parts of S. jambos have been used worldwide for treating diarrhea accompanied by fever, dysentery, sore throat, diabetes, and other infectious diseases. Endophytic fungi isolated from medicinal plants have high diversity, and the biological activity of their secondary metabolites is associated with their host. Therefore, this study aimed to determine the diversity of endophytic fungi from the stem bark of S. jambos and the antibacterial activity of secondary metabolites of endophytic fungi. Fungal isolates with high antibacterial activity were identified to obtain fungal species, and the structure of their compounds was determined. The disc diffusion method carried the antibacterial activity test against Gram-positive (Staphylococcus aureus and Bacillus subtilis) and Gram-negative (Escherichia coli and Salmonella typhi) bacteria. Characteristics of endophytic fungi were identified microscopically and macroscopically. Active endophytic fungi were identified by molecular analysis of the internal transcribed region (ITS) of the ribosomal DNA. Isolation of antibacterial compounds using chromatographic techniques and determination of chemical structures using spectroscopy was performed. Eight endophytic fungi were obtained from the stem bark of S. jambos, namely SJ1–SJ8. The endophytic fungus SJ6 showed the highest activity and base on phylogenetic analysis, was identified as Fusarium verticillioides. Pure compounds isolated as yellowish-white solids showed good antibacterial activity against S. aureus and S. typhi with minimum inhibitory concentration values of 64 g/mL each. Based on 1D and 2D nuclear magnetic resonance spectroscopic analysis, compound 1 was identified as 3-hydroxy-4-(hydroxy(4-hydroxyphenyl)methyl)dihydrofuran-2-on.